2018
DOI: 10.3748/wjg.v24.i24.2537
|View full text |Cite
|
Sign up to set email alerts
|

Glycoprotein biomarkers for the detection of pancreatic ductal adenocarcinoma

Abstract: Pancreatic cancer (PaC) shows a clear tendency to increase in the next years and therefore represents an important health and social challenge. Currently, there is an important need to find biomarkers for PaC early detection because the existing ones are not useful for that purpose. Recent studies have indicated that there is a large window of time for PaC early detection, which opens the possibility to find early biomarkers that could greatly improve the dismal prognosis of this tumor. The present manuscript … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 162 publications
0
17
0
Order By: Relevance
“…In general, cancer cells require a considerable nutrient supply for their rapid growth, and glucose has been proven to be their main source of energy [16]. Due to its extensive desmoplastic reaction, PC is characterized by hypovascularization [17], and pancreatic cancer cells are accordingly more dependent on a high level of glycolysis rather than oxidative phosphorylation [1719].…”
Section: Introductionmentioning
confidence: 99%
“…In general, cancer cells require a considerable nutrient supply for their rapid growth, and glucose has been proven to be their main source of energy [16]. Due to its extensive desmoplastic reaction, PC is characterized by hypovascularization [17], and pancreatic cancer cells are accordingly more dependent on a high level of glycolysis rather than oxidative phosphorylation [1719].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, blood-based CA 19-9 is widely used for diagnosis and prognosis in PC patients; however, due to its low sensitivity and specificity, clinical prediction is not satisfactory. Furthermore, there are CA 19-9-negative patients due to limited Lewis antigen [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…The study enabled one to assess specific glycosylation patterns in patients and also suggested therapeutics targets, such as glycoenzymes (Palmigiano et al, 2016). Simultaneous measurement of specific glycoforms combined with protein levels has been suggested to increase the diagnostic potential in pancreatic cancer (Llop et al, 2018). The majority of FDA-approved protein tumor markers currently used in clinical practice are glycoproteins, many of them showing glycosylation alterations in cancer (Lauc et al, 2016).…”
Section: Glycoproteomicsmentioning
confidence: 99%